ТАЛАБАЛАР ИНТЕЛЛЕКТУАЛ САЛОҲИЯТИНИ ОШИРИШДА МУСТАҚИЛ ТАЪЛИМ АҲАМИЯТИ - Юсупова, Ф.З. (SCIENCE and SOCIETY, 2017)
In the article are considered the questions of modernization of the self-study work at the lectures which are considered to be not only as a factor of strong assimilations of educational materials, but as a factor of evolution of the creative ability of students, skills to work independently and promoting to the increasing of intellectual potential.